Role of Endoscopic Ultrasound Elastography Strain Histograms in the Evaluation of Patients with Pancreatic Masses - Okasha, Hussein Hassan; El-Amin, Hussein; Sayed, Zain El-Abdeen; Maghraby, Ahmed Abd Elfadeel (Turkish Journal of Gastroenterology, 2021)
Background: The Endoscopic Ultrasound (EUS) quantitative elastography strain ratio (SR) and strain histogram (SH) methods for noninvasivepancreatic masses differentiation have been recently developed. The aim of this research was to investigate the accuracy of thediagnostic differentiation methods for patients with pancreatic masses, based on the EUS SR and SH.Methods: This is a prospective study involving 100 cases with pancreatic masses. Patients were classified into 2 groups: group thatwas diagnosed with pancreatic malignancy with positive histopathology by biopsy obtained by fine-needle aspiration or postoperativepathology (72 patients) and the group diagnosed with pancreatitis with negative pathology and follow-up for at least 1 year(28 patients).Results: Based on the ROC curve, the cut-off point for Mode 1 was set at 97. Values under it showed the presence of malignant pancreaticmasses. Mode 1 achieved a sensitivity of 89% and a specificity of 43% with an overall accuracy of 76%. The predictive positive valuewas 70%, and the predictive negative value was 60%. The cut-off point for SR was set at 3.04, and the values were equal or above thesuggested pancreatic malignancy. The SR achieved a sensitivity of 95.83%, a specificity of 61%, with an overall accuracy of 86%. Thepredictive positive and negative values were 86.2% and 85%, respectively.Conclusion: Mode 1 SH showed good sensitivity in the identification of pancreatic malignant tumors but were disappointingly of lowspecificity. Higher sensitivity, specificity, and overall accuracy were obtained by using the SR.